Gender and sexuality in the urban space analysis - Joseli Maria Silva (Geosul, 2007)
This study aims at analyzing the constituent elements of the relationship among poverty, gender and urban space, demonstrating the growth of women supporting their families located in low-income peripheral area. The investigation explores the geographical approach which focus on the association between space and gender and reveals the female everyday life and her spaciality starting from the symbolic and material power that regulates the contemporary spacial complexity.